1995
DOI: 10.1007/bf00036409
|View full text |Cite
|
Sign up to set email alerts
|

An immunocytochemical method for histamine: application to the planarians

Abstract: Histamine-immunoreactivity was investigated in the planarians Dugesia tigrina and Polycelis nigra . Specific antisera against a histamine-protein conjugate were used, and 1-ethyl-3 (3-dimethyl-aminopropyl) carbodiimide was used both as coupling agent to prepare the antigen and as a tissue fixative . In D. tigrina, histamine-immunoreactivity was restricted to photoreceptor cells in the cerebral eye . In P nigra, nerve fibers were found in the ventral nerve cord and nerves running laterally from these . The epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Wikgren et al (1990) demonstrated in different members of the Plathelminthes the occurrence of histamine in the nervous system and the distribution of histamine in the area of the excretory organs. Panula et al (1995) showed immunoreactivity in the region of the cerebral eye of Dugesia tigrina, but observed no histaminergic structures in the nervous system. On the other hand, they pointed out in Polycelis nigra that histaminergic immunoreactivity occurred in some fibres of the longitudinal nerves and lateral of the brain, but no immunoreactivity was observed in the area of the photoreceptors.…”
Section: Histaminementioning
confidence: 91%
“…Wikgren et al (1990) demonstrated in different members of the Plathelminthes the occurrence of histamine in the nervous system and the distribution of histamine in the area of the excretory organs. Panula et al (1995) showed immunoreactivity in the region of the cerebral eye of Dugesia tigrina, but observed no histaminergic structures in the nervous system. On the other hand, they pointed out in Polycelis nigra that histaminergic immunoreactivity occurred in some fibres of the longitudinal nerves and lateral of the brain, but no immunoreactivity was observed in the area of the photoreceptors.…”
Section: Histaminementioning
confidence: 91%
“…Small numbers of histaminergic fibres have been demonstrated immunocytochemically in the turbellarians, Microstomum lineare and Polycelis nigra, and in the cestode, Diphyllobothrium dendriticum, where they are scattered mainly in the longitudinal nerve cords (Wikgren et al 1990). Histamine has also been demonstrated immunocytochemically in the turbellarian, Dugesia tigrina, but not in the CNS; rather, it was found to be restricted to photoreceptor cells in the cerebral eye, with preliminary evidence that its occurrence may exhibit some circadian variation (Panula et al 1995). Since HA is a well established neurotransmitter of photoreceptors in higher invertebrates, notably insects, further study of this phenomenon would seem appropriate.…”
Section: Histaminementioning
confidence: 99%
“…y-Amino butyric acid (GABA) is a recognised important inhibitory neurotransmitter of widespread occurrence in both vertebrates and invertebrates; surprisingly, there are only three reports of its presence in flatworms. Using two independent immunocytochemical methods, involving a monoclonal antibody specific for GABA, combined with different fixation protocols, Eriksson & Panula (1994) and Eriksson, Panula & Reuter (1995 a), Eriksson et al (19956) have demonstrated extensive immunoreactivity for this biogenic amine in fibres in the central nervous system of the turbellarians, Polycelis nigra and Dugesia tigrina, in the longitudinal nerve cords and nerve nets of Moniezia expansa and in the longitudinal cords and lateral nerves in the posterior portion of Fasciola hepatica. HPLC analysis confirmed the presence of GABA in the two parasitic worms, but revealed a much higher concentration of the amine in the cestode.…”
Section: Y-amino Butyric Acidmentioning
confidence: 99%
“…Using this fixation, histamine was demonstrated more clearly than with other fixatives. This type of fixation is now recommended for histamine immunocytochemistry (Panula et al, 1995;Eriksson et al, 1996Eriksson et al, , 1998. In our previous experiments using this method, the presence of histamine and serotonin was demonstrated in the nucleus of mast cells (Csaba et al, 2006).…”
Section: Introductionmentioning
confidence: 99%